Upaya Hukum Alternatif Penyelesaian Sengketa: Studi Kasus Keterlambatan Upah Pekerja - Arya Bagus Pratama; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
Late payment of wages is a recurring issue in Indonesia that requires a fair and effective resolution. This article aims to examine the legal measures of Alternative Dispute Resolution (ADR) in addressing late wage payments. The research uses a juridical-normative approach, analyzing concepts, theories, expert opinions, and relevant laws such as the APS Law, PPHI Law, Manpower Law, and Government Regulation No. 36 of 2021 concerning Wages. The findings indicate that ADR mechanisms, including negotiation, conciliation, mediation, and arbitration, are more efficient compared to litigation, which is time-consuming and costly. Success factors for ADR include effective communication between the parties, the participation of a neutral mediator or conciliator, a skilled arbitrator, and a legally binding agreement. Therefore, ADR offers an effective solution to achieve justice and maintain harmony in industrial relations. This article suggests strengthening regulations and promoting awareness of these mechanisms among stakeholders in the employment sector